PENGARUH METODE PEMBUATAN DAN PEREBUSAN DALAM EKSTRAK TEH TERHADAP KUALITAS MIKROBIOLOGI TELUR ASIN AYAM RAS - Dyah Nurul Afiyah; Nur Soleh (Universitas Islam Kadiri, 2016)
The microbiologi (Salmonella-Shigella) test on the egg chiken salt is one type with two treatment this is production egg salt chiken method and extract tea boiled that different level. Sample was collected from the factorial RAL analysis. Microbe identification to Center of Biotechnology Development Laboratory, Muhammadiyah University of Malang. Result showed from factorial RAL Analysis there is no effect (non significant) (P>0,05) this abouth coloni microorganisme Salmonella-Shigella total.